Exploration of the Sufferings of Refugee Children: A Semiotic Study of Picture Books - Nayab, Durr-e-; Bashir, Ayesha; Naeem, Urwa (Pakistan Journal of Humanities and Social Sciences, 2023)
The present study aims to highlight the sufferings of refugee children through the sign language used in two picture books and the main objective has been to explore the ways, the characters adopted to confront all the challenges of their lives. As for as the methodology of this study is concerned, it is based on the qualitative method. Kress and Leeuwen's (2006) modal of visual grammar is applied as a theoretical framework for this study. The findings revealed that although the characters of these picture books have gone through crucial circumstances in the course of the war they still practiced good values and didn’t let their souls be corrupted in any way. In this way, they set a glorious example for all the children across the world. Moreover, through this study, the researcher is hopeful that it will help out the language classroom in several ways as to promote good values among the learners, to enable them to understand and analyze the texts through the pictures illustrated in their books and develop interesting non-verbal activities for them to enhance their social, intellectual and emotional development.